Comparative analysis of developmental outcomes in very preterm infants: BSID-II versus Bayley-III German norms. - Marlene Hammerl; Martina Zimmermann; Anna Posod; Ulrike Pupp Peglow; Michaela Höck; Elke Griesmaier; Ursula Kiechl-Kohlendorfer; Vera Neubauer (PLoS ONE)
Introduction After the release of the Bayley Scales of Infant and Toddler Development, third edition (Bayley-III), US norms, an overestimation of outcome was observed. But, the conformity between the Bayley Scales of Infant Development, second edition (BSID-II), and the Bayley-III German norms is unknown. This retrospective analysis aimed to compare outcomes of very preterm infants tested with BSID-II and Bayley-III German norms. Methods Infants born from November 2007 to July 2018 were included. Exclusion criteria were death or missing outcome. Infants underwent testing with either BSID-II until December 2013 or Bayley-III from January 2014 onward, at 12 and/or 24 months. BSID-II Mental Developmental Index (MDI) was compared to Bayley-III cognitive score and a combined Bayley-Score (CB-III) consisting of the cognitive and language composite score. BSID-II Psychomotor Developmental Index (PDI) was compared to Bayley-III motor composite score. Abnormal outcomes were defined as scores <85 (delay) or <70 (impairment). Results 649 infants were included. At 12 months, the Bayley-III cohort achieved higher scores in all domains compared to the BSID-II cohort (all p<0.05), with lower rates of motor delay in the Bayley-III cohort (p<0.001). At 24 months, only Bayley-III motor composite scores were higher than the BSID-II PDI (p<0.001). Rates of cognitive impairment were higher in the Bayley-III cohort (p = 0.013). Interpretation Our findings indicate that the Bayley-III German norms effectively identify children needing interventions, particularly at 24 months corrected age. This supports both clinical application and scientific comparability with the BSID-II.